Transcatheter device closure of atrial septal defects: More to think about than just closing the hole - O’Byrne, Michael L (Curr Opin Cardiol, 2018)
PURPOSE OF THE REVIEW: To review current controversies in the transcatheter device closure of ostium secundum atrial septal defects (ASD). RECENT FINDINGS: Trans-catheter device closure of ASD (TC-ASD) has well-established efficacy and safety. For most individual patients with suitable anatomy, TC-ASD is the preferred method for treating ASD. The availability of large multicenter datasets has made it possible to study practice patterns at a range of hospitals across the United States. These studies have revealed differences in practice that were not previously appreciated. 1) Interpretation of the indications for TC-ASD, specifically the definition of right ventricular volume overload varies between hospitals. 2) In response to concern about device erosion, an increasing proportion of patients are being referred for operative ASD closure. 3) Over the last decade, the average age at which ASD closure occurs has decreased. These trends demonstrate previously under-appreciated differences in opinion between cardiologists across the country, and suggest that further research is necessary to address knowledge gaps limiting consistency of practice. SUMMARY: As TC-ASD and congenital interventional cardiology mature as a field, studies of real-world practice provide increasingly valuable information about aspects of care where there are disagreements about best practices and where further research is necessary.